PENGARUH KOMPETENSI, KOMUNIKASI, DAN KECERDASAN EMOSIONAL TERHADAP KINERJA DOSEN DI SEKOLAH TINGGI PARIWISATA SAHID SURAKARTA - Artanti, Evy Febri; Suddin, Alwi; Wardiningsih, Suprihatmi Sri (JURNAL MANAJEMEN SUMBER DAYA MANUSIA, 2019)
This research is conducted to know the significance between;(1) the competence, (2) the communication, and (3) the emotional intelligence to the performance of lecturer at Sekolah Tinggi Pariwisata Sahid Surakarta. The sample is taken by census. The technique of collecting the data is using questioner through validity and reliability test. The analysis technique uses double regression with classical assumption. The analysis results which could be reported are; from the validity test, the variable instruments are valid. The reliability test is reliable. From the classical assumption, multicollinearity test is no multicollinearity, heteroskedasticity test is no heteroskedasticity, autocorrelation test is no autocorrelation, and normality test is normal. The analysis result shows that: there is a significant effect of competence to the performance of Lecturer, there is a significant effect of communication to the performance of Lecturer, and there is a significant effect of emotional intelligence to the performance of Lecturer.